A preliminary, quantitative study on the use of traditional and complementary medicine by cancer patients seen at the Senkatana oncology clinic, Maseru, Lesotho - Mopa A. Sooro; Thabo S. Thoahlane; Maseabata V. Ramathebane; Kabelo A. Mputsoe (BMC, 2024)
Abstract Background The use of traditional and complementary medicine (TCM) by cancer patients remains common in several countries especially in the Sub-Saharan Africa. However, the reasons for use are complex and change with time and geographic location, they may vary from therapy to therapy, and they are different from one individual to another. The use of TCM has been associated with active coping behaviour and a way through which patients take control of their own health. However, cancer patients do not disclose their use of TCM to the attending healthcare professionals and therefore the effects of these medicines on the patients may not be ascertained. Aim To investigate the use of traditional and complementary medicines among patients diagnosed with cancer. Methods A cross-sectional, quantitative study was conducted at Senkatana Oncology clinic in May to June 2023. Cancer patients underwent standardized, quantitative interviews using structured questionnaires about their use of TCM. Descriptive statistics were used to analyse the data. Logistic regression analysis was also used to identify factors associated with satisfaction with the performance of TCM. Results All interviewed patients (n = 50, 100%) reported to be using TCM. Patients consisted of 24 females (48%) and 26 males (52%) in the age range 14 to 82 years old. The majority of the study population was in the age group 35-44 years old. The most prevalent cancer among participating males was prostate cancer and among females was cervical cancer. Biological products use was the most prominent with the highest average percentage usage (14.7%). The majority of patients (66%, n = 33) indicated that they just wanted to try everything that could help. Patients (n = 47, 94%) further reported that they had been using complementary medicine during the same period as they were using conventional treatment so that both may work to help each other. Neither gender nor age predicted satisfaction with the performance of traditional and complementary medicine. Conclusions It is concluded that all interviewed cancer patients use TCM. Patients indicated that one of the reasons for using TCM was that they wanted to try everything that could help in their cancer care. Patients further reported that they did not inform their oncologist of their concurrent use of TCM because they had been advised not to use other medicines besides what they are given at the clinic.